Exploring Job Application Letters of EFL Learners - Utami Rosalina; Yeni Noryatin; Veronika Simbolon; Ninik Hernika; Salsabila Nuravianti (Journal on Education, 2023)
The background to this analysis is that many companies require applicants to write their application letters in English. If a student wishes to get a job, a job application letter is required upon leaving school. The purpose of this study is to examine EFL learners’ application letters. This study uses a qualitative methodology and discourse analysis as its research design. The data used in qualitative research comes from a variety of application letters. Participants in this study were high school students at a vocational school. It consists of four students in grade 12—two boys and two girls. The research was conducted through an analytical process in which a student completed her application within one week. They are then collected and analyzed by researchers. The general structure of job application letters is analyzed, and formal and informal words in job application letters are recognized and noted. In general, the results of the above analyses show that two students met the criteria for writing a job application letter, while the other two students did not yet meet the criteria for writing a job application letter. Teachers should pay more attention to teaching writing subjects, especially in making sentences such as when writing a job application letter. If you find an error while writing, explain of the errors to avoid mistakes from happening again and reduce error at the start.